2014
DOI: 10.1088/1751-8113/47/31/315206
|View full text |Cite
|
Sign up to set email alerts
|

Electrons in deterministic quasicrystalline potentials and hidden conserved quantities

Abstract: Abstract. We propose an ansatz for the wave function of a non-interacting quantum particle in a deterministic quasicrystalline potential. It is applicable to both continuous and discrete models and includes Sutherland's hierarchical wave function as a special case. The ansatz is parameterized by a first cohomology class of the hull of the structure. The structure of the ansatz and the values of its parameters are preserved by the time evolution. Numerical results suggest that the ground states of the standard … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 56 publications
(169 reference statements)
3
38
0
Order By: Relevance
“…One can define environment-specific distributions, N (t) µ (h), where µ denotes the local environment. There are three different local environments on the Fibonacci chain which we define according to the nature of the arrow immediately following the site, namely, µ = r, l, u, appearing with the frequencies (15). The N (t) µ (h) give the number of times height h is found on the local environment µ in region R t .…”
Section: Diffusion Equation For the Height Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…One can define environment-specific distributions, N (t) µ (h), where µ denotes the local environment. There are three different local environments on the Fibonacci chain which we define according to the nature of the arrow immediately following the site, namely, µ = r, l, u, appearing with the frequencies (15). The N (t) µ (h) give the number of times height h is found on the local environment µ in region R t .…”
Section: Diffusion Equation For the Height Functionmentioning
confidence: 99%
“…Although this Hamiltonian is simple, no solutions were known for any of its eigenstates, apart from trivial confined eigenstates at the middle of the spectrum [17]. This situation changed recently, when Kalugin and Katz [15], building on the work of Sutherland [35], deduced the form of the ground state of the Hamiltonian (1) on the Penrose and Ammann-Beenker tilings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The scaling factor κ is related to λ = e 2κ defined in Ref. [29], where it was numerically found that λ = 1.07500(1) for the ground-state wave function of the Penrose tiling. When plugged in (D2) and (D3), this gives β = 0.9991897(2), in agreement with the above numerical result.…”
Section: Commensurate Penrose Tiling and Underlying Square Latticementioning
confidence: 99%
“…The perpendicular space images of eigenstates in the one-dimensional Fibonacci chain [20] and spin models on quasicrystals [21] have been investigated. Perpendicular space images have been calculated for particular eigenstates satisfying an ansatz [22] for two-dimensional tight-binding models [23].…”
Section: Introductionmentioning
confidence: 99%